ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH SUMATERA SELATAN - Hibzon Hibzon (Jurnal Ekonomi Pembangunan, 2007)
The purposed of this research is to analize the factors with influence Pendapatan AsliÂ  Daerah (PAD) of South Sumatera Province. Data used in this research is secondary, such as gross domestic product, PAD, Population, and income percapita. Estimated regression show there is positive correlation between PAD, population, economics growth and income percapita. Key Words : PAD, economic growth, population, income percapita.